Community Engagement: Knowledge Transfer Program at SMUM Taufikiah Asriah, Tg Besar, Kuala Lipis - Azizan, Ramli (Faculty of Industrial Sciences and Technology, UMPSA, 2024)
On the 8th and 9th of May 2024, SMUM Taufikian Asriah, Tg Besar, Kuala Lipis, under Majlis Ugama Islam dan Adat Resam Melayu Pahang (MUIP), hosted a dynamic knowledge transfer program focused on ethics, integrity, and occupational safety and health (OSH).